Behaviour of solar wireless sensor network in saharan region under different scenarios consideration - Boubakeur Hamlili; Khelifa Benahmed; Brahim Gasbaoui (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper deals with the Wireless Sensor Network comportment in the south west region precisely Bechar city. Algeria has the highest technical and economic potentials for solar power exploitation in the Middle East and North Africa region. In this paper, the focus is on the behaviour of Wireless Sensor Network (WSNs) supplied by solar panel PV connected to node via boost converter (DC/DC) controlled by maximum power point tracking (MPPT) technique, using the incremental conductance (IC) algorithm to extract maximum power. In Our present work, many tests were carried out. The WSNs are examined under sever and different temperature and irradiation variation. The obtained result is satisfactory for our (WSNs) simulated in a MATLAB / SIMULINK environment. The performances of the proposed strategy controller give a satisfactory simulation results.